Simultaneous Anti-Tuberculosis and Anti-Tumor Treatment with Immune Checkpoint Inhibitors for Co-Existent Pulmonary Tuberculosis and Advanced Lung Cancer - Wang H; Gao L; Cai X; Li J; Lang Y; Zheng R; Yang S (Infection and Drug Resistance)
Huaichong Wang,1 Liujie Gao,2 Xinjun Cai,1 Jinmeng Li,1 Yuying Lang,1 Ren Zheng,1 Shengya Yang3 1Department of Pharmacy, Hangzhou Red Cross Hospital, Hangzhou, Zhejiang Province, People’s Republic of China; 2Department of Oncology, Hangzhou Red Cross Hospital, Hangzhou, Zhejiang Province, People’s Republic of China; 3Tuberculosis Diagnosis and Treatment Center, Hangzhou Red Cross Hospital, Hangzhou, Zhejiang Province, People’s Republic of ChinaCorrespondence: Shengya Yang, Tuberculosis Diagnosis and Treatment Center, Hangzhou Red Cross Hospital, East Huancheng Road No. 208, Hangzhou, Zhejiang Province, People’s Republic of China, Email 15967116949@163.comBackground: Immune checkpoint inhibitors (ICIs) have emerged as the first-line treatment for driver-negative advanced non-small cell lung cancer (NSCLC). However, there is uncertainty regarding the availability and timing of ICI initiation in patients with NSCLC combined with pulmonary tuberculosis (TB). Additionally, the implementation of dual therapy for anti-TB and anti-tumor treatment poses significant challenges in terms of avoiding drug–drug interactions and reducing adverse reactions during clinical diagnosis and treatment.Case Description: A 65-year-old male patient was admitted to our designated TB hospital following an out-of-hospital TB diagnosis. Relevant examinations were completed after admission, and chest computed tomography revealed that the patient had lung squamous cell carcinoma with multiple metastases in lymph nodes and liver. A multidisciplinary team (MDT) consisting of oncologists, pulmonologists, and clinical pharmacists followed evidence-based practices to determine treatment options. They evaluated the benefits and risks of ICIs and performed therapeutic drug monitoring for the dual treatment of anti-TB and anti-tumor drugs. After 18 days of anti-TB treatment, the patient successfully received ICIs combined with chemotherapy for NSCLC while continuing anti-TB therapy. The patient’s anti-TB treatment plan was adjusted due to gastrointestinal reactions, bone marrow suppression, and liver function injury. Ultimately, both NSCLC and pulmonary TB were effectively controlled.Conclusion: For patients with NSCLC complicated by pulmonary TB, after 2– 4 weeks of effective anti-TB treatment, anti-tumor therapies, including ICIs, can be simultaneously implemented with the anti-TB treatment. Therapeutic drug monitoring is beneficial for avoiding serious adverse effects and ensuring the timely treatment of both diseases.Keywords: anti-tumor therapy, immunotherapy, Mycobacterium tuberculosis, adverse effects